1993
DOI: 10.1002/cne.903280107
|View full text |Cite
|
Sign up to set email alerts
|

Physiological properties and morphological characteristics of cutaneous and mucosal mechanical nociceptive neurons with A‐δ peripheral axons in the trigeminal ganglia of crotaline snakes

Abstract: Primary A-delta nociceptive neurons in the trigeminal ganglia of immobilized crotaline snakes were examined by intrasomal recording and injection of horseradish peroxidase in vivo. Thirty-four neurons supplying the oral mucosa or facial skin were identified as A-delta nociceptive neurons which responded exclusively to noxious mechanical stimuli and had a peripheral conduction velocity ranging from 2.6 to 15.4 m/s. These neurons were subdivided into a fast-conducting type (FC-type) and a slowly conducting type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Nociceptors have been identified and characterized in both taxa; detailed studies on crotaline snakes have demonstrated the presence of C fiber and A-delta fiber types that respond to noxious stimulation (75,76,144), and frogs also possess nociceptors (42). Liang and Terashima (75,76) found the majority of nociceptive neurons in crotaline snakes were A-delta, performing the same function as mammalian C fibers. Some 34 A-delta fibers were characterized in 9 snakes, whereas only 10 C fibers, of which 5 were nociceptive, were described (144).…”
Section: Amphibians and Reptilesmentioning
confidence: 99%
“…Nociceptors have been identified and characterized in both taxa; detailed studies on crotaline snakes have demonstrated the presence of C fiber and A-delta fiber types that respond to noxious stimulation (75,76,144), and frogs also possess nociceptors (42). Liang and Terashima (75,76) found the majority of nociceptive neurons in crotaline snakes were A-delta, performing the same function as mammalian C fibers. Some 34 A-delta fibers were characterized in 9 snakes, whereas only 10 C fibers, of which 5 were nociceptive, were described (144).…”
Section: Amphibians and Reptilesmentioning
confidence: 99%
“…1,2 For reptiles in particular, there are several challenges to effectively detecting and assessing nociception and there is a general lack of knowledge regarding effective antinociception in these species. 3,4,5 Reptiles have the necessary neuroanatomic structures to detect pain, 5,6,7 and conditions considered painful in humans and domestic pets are assumed to be painful in reptiles. 3 Unfortunately, antinociceptive drugs that are effective in one vertebrate class are not necessarily effective in other vertebrate classes.…”
mentioning
confidence: 99%
“…Multiple studies in different reptile species have demonstrated the presence of the neuroanatomical apparatus for sentience and nociception (Liang & Terashima 1993;ten Donkelaar & de Boer-van Huizen 1987). It has been shown that environmental stimuli elicit impulse transmission from sensory receptors, through the spinal cord, to the animal's brain.…”
Section: Respiratory Systemmentioning
confidence: 99%